2014
DOI: 10.1111/echo.12812
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Strain before and after Pulmonary Thromboendarterectomy in Patients with Chronic Thromboembolic Pulmonary Hypertension

Abstract: In patients with CTEPH, RV basal strain paradoxically became less negative (i.e., relative systolic shortening decreased) following PTE. This change in RV strain could be due to intraoperative RV ischemia and/or postoperative stunning. Thus, RV basal strain cannot be used as a surrogate marker for surgical success early after PTE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
(40 reference statements)
3
19
0
Order By: Relevance
“…found a similar decrease (i.e., a change toward 0%) in RV basal free wall strain and lack of correlation with PVR after PTE. Thus, although some echocardiographic parameters correlate well with successful PTE (e.g., tricuspid regurgitation velocity, RV Tei index), others clearly do not (e.g., RV free wall strain, TAPSE) . As our study had only short‐term follow‐up, we cannot comment on longer‐term RV remodeling post‐PTE …”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…found a similar decrease (i.e., a change toward 0%) in RV basal free wall strain and lack of correlation with PVR after PTE. Thus, although some echocardiographic parameters correlate well with successful PTE (e.g., tricuspid regurgitation velocity, RV Tei index), others clearly do not (e.g., RV free wall strain, TAPSE) . As our study had only short‐term follow‐up, we cannot comment on longer‐term RV remodeling post‐PTE …”
Section: Discussionmentioning
confidence: 77%
“…They also found mild improvement in TAPSE after subsequent follow‐up, but to a level less than preoperative values. In addition, Marston et al . found a similar decrease (i.e., a change toward 0%) in RV basal free wall strain and lack of correlation with PVR after PTE.…”
Section: Discussionmentioning
confidence: 86%
“…Speckle tracking is today widely accepted in the context of functional assessment of the left ventricle. In the last few years, there has been increasing interest in the use of this technique for RV analysis [31][32][33][34][35][36][37][38]. Compared to other markers of function, strain measurements have been reported to be angle-independent, less loadsensitive and able to accurately reflect regional deformation.…”
Section: Fig 4 Results Of Linear Regression (Top) and Bland-altman (mentioning
confidence: 99%
“…The assessment of RV longitudinal systolic function by GLS of the RV seems promising, but future studies must determine the usefulness of this parameter as a marker of systolic function following heart surgery, including surgery in CTEPH patients undergoing PEA. Marston N et al demonstrated that RV basal strain paradoxically became less negative following PEA and should therefore not be used as a marker for success early after PEA …”
Section: Discussionmentioning
confidence: 99%